FROM ADVANCE TO TRANS-PROFESSIONAL EDUCATION - A. G. Kislov (Obrazovanie i Nauka, 2018)
Introduction. For several decades, the gap of vocational education with quickly changing realities in labour market, in the field of technologies and socio-economic sphere, and the need for the advancing vocational training, have been considered as the topical and steadily growing problems. Numerous attempts to overcome the presented above problems by means of fundamentalization and predictive methods have not led to anything so far. It is obvious that other education opportunities for in-demand, highly skilled, competitive specialists are needed.The aims of the publication are to discuss the potential of trans-professional education; to come up with arguments in favour of its introduction as the most perspective direction which might allow university and college graduates: to be guided better on labour market; to be more confident in unstable, unpredictable reality; to adapt quickly to dynamically changing situations in the world of professions.Methodology and research methods. The research paper is based on comparative analysis that provided an opportunity to find out the conceptual grounds of traditional mono-professional education and trans-professional education appropriate for challenges of modern Russia.Results and scientific novelty. It is emphasized that mono-professionalism as a paradigm reference point of professional education content is called for global reconsideration; for many years, preservation of traditional forms and methods have prevented mono-professionalism of good intentions to give it the advancing character, especially, at its initial stage.For the first time, trans-professional education has been considered as a result of considerably heterogeneous (as opposed to homogeneous) bi- and polyprofessional training; the essence of that training consists in learning not related specialties concerned to one professional group, but professions that are absolutely far apart. Such approach will promote not only expansion of professional opportunities among graduates of educational institutions, but even emergence of students’ readiness to be beyond professional stereotypes.Practical significance. The guidelines for further development of the Russian vocational education at various levels are suggested.